Association between Body Mass Index and Prevalence of Asthma in Korean Adults - Kang, Min (Chonnam Med J, 2020)
We evaluated the association between body mass index (BMI) and the prevalence of asthma. Using data from the 2015 Korean Community Health Survey, 214,971 participants aged between 19 and 106 years were included in this study. Asthma was defined based on the self-report of physician diagnosis. BMI was classified as underweight (<18.5 kg/m(2)), normal weight (18.5 kg/m(2)≤BMI<23.0 kg/m(2)), overweight (23.0 kg/m(2)≤ BMI<27.4 kg/m(2)), and obese (≥27.5 kg/m(2)) based on the BMI categories for Asians by the World Health Organization. Multiple logistic regression analysis was performed with sampling weights to evaluate the association between BMI and asthma after adjusting for age, educational level, income, type of residential area, smoking status, alcohol consumption, physical activity, hypertension, and diabetes. In men, BMI had an inverted J-shaped association with the prevalence of asthma, with an odds ratio of 1.88 (95% confidence interval [CI]: 1.89–2.24) for underweight and 1.12 (95% CIs: 0.97–1.29) for obesity. In women, BMI had a J-shaped association with the prevalence of asthma, with an odds ratio of 1.05 (95% CIs: 0.91–1.22) for underweight and 2.29 (95% CIs: 2.06–2.56) for obesity. In conclusion, in a nationally representative sample of Korean adults, the association between BMI and the prevalence of asthma varied between the sexes. This suggests that malnutrition and obesity are involved in the pathophysiology of asthma.